The Structural Safety Assessment of the Overloaded Members of Highway Bridges - Antanas Kudzys (The Baltic Journal of Road and Bridge Engineering)
A residual reliability index of load-carrying structures of existing highway bridges overloaded by unforeseen vehicular live loads is discussed. The primary and inspection structural safety margins of particular members of bridges are considered. The primary and revised survival probabilities of intact particular members are analysed. Target reliability indices of the structural members of road bridges are presented. A transformed Bayes theorem in the analysis of revised failure probabilities of overloaded members of highway bridges is recommended. The Bayesian approach is combined with the method of transformed conditional probabilities for series systems. The simple calculation of revised reliability indices of particular members is demonstrated by a numerical example.